References on the english language in reports of students and egresses in the graduate course in spanish - Yokota, Rosa (Universidade Estadual Paulista, 2016)
This article is based on a broader study developed by Rodrigues and Yokota (2013) on the profile of licensed students in Languages-Spanish in São Paulo State. We present a cutout of data and deepened reading and analysis, basing ourselves on the Critical Discourse Analysis (CDA), on how the survey participants refer (or not) to the language. References on the English language show a strong influence of experience with this language in choosing the course of Spanish as a foreign language. The imagery created on foreign languages by Brazilian students is crossed by the experiences they had with the English language. Recognizing this foundational relationship, whether positive or negative, is necessary to establish the relationship with the new foreign language being studied or, in the case of university teachers of foreign languages, mediate student’s relationship with the new language.